Moving music: exploring movement-to-sound relationships - Schacher, J. C. (Proceedings of the 3rd International Symposium on Movement and Computing, 2016)
Relating movement to sound in an artistic context demands an understanding of the foundations of perception of both domains and the elaboration of techniques that effectively creates a link with technical means from body to sound. This article explores the strategies necessary in interactive dance work to successfully link movement to sound processes. This is done by reducing the dimensions of the observed elements to the fundamentals and at the same time identifying target dimensions that allow the recreation of an equivalent expression. A categorisation helps to elucidate those elements and characteristics that can be applied and looks at how they are perceived by the audience. The asymmetry that arises when using technical links to generate sound in interactive dance poses the question of dependency and exposes limits and challenges of using technology in this performing arts practice.